2022
DOI: 10.3389/fnut.2022.969512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and macrophages immunomodulatory activity of two water-soluble polysaccharides from Abrus cantoniensis

Abstract: The study aims to elucidate the physicochemical properties and immunomodulatory activity of two polysaccharides (ACPt0 and ACPt2) from Abrus cantoniensis. Results revealed that ACPt0 with a molecular weight of 26.0 kDa, was mainly composed of glucose (83.1%) and galactose (6.1%), and that ACPt2 with a molecular weight of 145.6/8.9 kDa, consisted of galactose (25.6%), galacturonic acid (22.2%), arabinos (16.6%) and galactose (11.0%) respectively. AFM and Congo red experiments suggested that ACPt0 and ACPt2 migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…TLR4 has been identified to be an important membrane receptor for mediating the effects of plant polysaccharides on the activation of immune cells [43,44]. Many studies have shown that plant polysaccharides can activate the NF-κB and MAPK signaling pathways through TLR4 receptors, and promote the release of related cytokines, and exert their immunoregulatory functions [45][46][47]. Yang et al (2020) found that Artemisia polysaccharides can activate the MAPK and NF-κB signaling pathways mediated by TLR4/TLR2 and significantly improve the immunomodulatory activity of immune cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 has been identified to be an important membrane receptor for mediating the effects of plant polysaccharides on the activation of immune cells [43,44]. Many studies have shown that plant polysaccharides can activate the NF-κB and MAPK signaling pathways through TLR4 receptors, and promote the release of related cytokines, and exert their immunoregulatory functions [45][46][47]. Yang et al (2020) found that Artemisia polysaccharides can activate the MAPK and NF-κB signaling pathways mediated by TLR4/TLR2 and significantly improve the immunomodulatory activity of immune cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this extract significantly increased the viability of RAW 264.7 cells, reaching 181% at a concentration of 15.6 µg/mL (Figure 5A). Thus, compounds activating macrophages promise to improve the host immune system ability [62][63][64][65].…”
Section: Effect Of Psht In Raw2647 31 Cell Viability Assaymentioning
confidence: 99%
“…Interestingly, this extract significantly increased the viability of RAW 264.7 cells, reaching 181% at a concentration of 15.6 µg/mL (Figure 5A). Thus, compounds activating macrophages promise to improve the host immune system ability [62][63][64][65]. A previous study reported that natural polysaccharides (LDP-1) extracted from the fruiting bodies of a rare wild Lactarius delicious with a molecular weight of 9.8 × 10 5 Da are…”
Section: Effect Of Psht In Raw2647 31 Cell Viability Assaymentioning
confidence: 99%